2009
DOI: 10.1007/s00265-009-0743-4
|View full text |Cite
|
Sign up to set email alerts
|

Song amplitude and body size in birds

Abstract: Bird song is a sexually selected multidimensional signal. A fundamental question regarding the evolution of sexually selected signals is what information they convey and how their honesty is maintained. Song amplitude is a performance-related signal trait that varies considerably between individuals, but this signal dimension has been neglected in past studies. I found that median song amplitude in male nightingales (Luscinia megarhynchos) and zebra finches (Taeniopygia guttata) did not vary significantly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…However, in other studies, many song characteristics failed to predict the body size of songbirds (Brumm 2009;Geberzahn et al 2009;Miyashita et al 2016). In these studies, song bandwidths, song rate, average frequency, song amplitude and repertoire size of the total song showed no relationship to body size.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, in other studies, many song characteristics failed to predict the body size of songbirds (Brumm 2009;Geberzahn et al 2009;Miyashita et al 2016). In these studies, song bandwidths, song rate, average frequency, song amplitude and repertoire size of the total song showed no relationship to body size.…”
Section: Introductionmentioning
confidence: 78%
“…We measured tarsus length (± 0.1 mm) 3 times at each capture, and used the average length as an indicator of body size. We used tarsus length as our measure of body size for the following three reasons: (1) it is observed to predict male quality and female choice in some birds (Kempenaers et al 1992;Møller & Ninni 1998;Hall et al 2013); (2) it has an observed relationship with call frequency (Price et al 2006;Brumm 2009;Geberzahn et al 2009;Linhart & Fuchs 2015); and (3) it is constant in adults.…”
Section: Body Size Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can suppose that crested auklets do not tune their individual vocal characteristics in response to such social environmental changes, but our data do not prove the absolute absence of vocal plasticity in adult crested auklets. Further observations are needed to test the effect of other factors such as population density or challenging by a rival that could cause call modifications in animal species both with and without vocal learning (e.g., Howard and Young 1998;Penteriani 2003;Brumm 2009) on acoustic variables of crested auklets calls. Appendix A…”
Section: Resultsmentioning
confidence: 98%
“…In the American bison, Bison bison , a negative relationship between vocal amplitude and male quality has been found [43]. A negative correlation between body size and maximum song amplitude during interactive singing was also found for nightingales, while there was no correlation for two other songbird species [44].…”
Section: Introductionmentioning
confidence: 91%